Tannins and Their Impacts on Animal Nutrition - Esin Ünver; Aylin Ağma Okur; Emre Tahtabiçen; Burak Kara; Hasan Ersin Şamlı (Turkish Journal of Agriculture: Food Science and Technology)
Tannins are phenolic metabolites, which naturally produced by plants. They can defend plants against pathogen microorganisms and viruses. According to animal nutrition, tannins have both adverse and beneficial effects depending on animal species, physiological state of the animal, structure and concentration of the tannins. The objective of this study was to review the literature about tannins, their effects and usage of tannins in animal nutrition.